Does Employee Performance Affect Customer Loyalty in Pharmacy Services? - Rabbanee, Fazlul; Burford, Oksana; Ramaseshan, Balasubramani (Emerald Group Publishing, 2015)
Purpose: Employees in community pharmacies play a far significant and distinct role compared to the employees in traditional retail stores. This paper examines the effects of employee performance on customer loyalty of pharmacy services. Design/methodology/approach: Data were collected through a self-administered survey filled in by the customers of 25 community pharmacies. A total of 679 completely filled-in questionnaires were analysed. The proposed model was tested through structural equation modelling using AMOS 22. Findings: Employee performance positively affects pharmacy customers’ perceived value, trust and loyalty. Perceived value and trust fully mediates the relationships between employee performance and customers’ attitudinal and behavioural loyalty. Unlike short term customers, the long term relational customers’ perceived value was found to have significant impact on their trust and behavioural loyalty. Research limitations: This study is based on the Australian community pharmacy industries; hence, caution must be exercised in the generalization of the results to other countries. The study has considered only perceived value and trust in examining the link between the employee performance and customer loyalty. Other variables such as commitment could possibly influence the link, which has not been considered in this study. Originality/value: The study contributes to the existing literature by focusing on how employee performance influences both attitudinal and behavioural loyalty of pharmacy customers. It shows empirical evidence that employee performance influences customers’ perceived value and trust en-route to influencing their loyalty. The study measures employee performance based on both empathy and service provider performance covering a broader spectrum of the construct.